Complete Denture Impression Procedures and Techniques Practised by Dental Surgeons of a Dental College in Eastern Part of India: A Short Survey (Global Journal of Medical Research, 2019)
One of the key factors contributing to the success of Complete Denture (CD) fabrication is proper impression making, though it varies from clinician to clinician. This survey aims to find out the current trend of impression making for CD practiced by a group of clinicians attached to Guru Nanak Institute of Dental Sciences and Research, Kolkata. A pre-tested questionnaire consisting of 15 questions with multiple options about impression making for CD was distributed amongst 150 practitioners. Received data were tabulated and analyzed using Microsoft Excel software. Total of 124 respondents returned duly filled questionnaires. 99.2% of practitioners made both primary and final impression. The material of choice for primary impression was impression compound (70.2%).
Keywords: survey; CD impression; disinfection; border molding; custom tray; sterilization